THE ROLE OF ZOOPLANKTON PREDATOR, CHAETOGNATHS (SAGITTA SPP) IN BAGUALA BAY WATERS, AMBON ISLAND - Niette.V. Huliselan (JOURNAL OF COASTAL DEVELOPMENT, 2002)
Study on the chaetognaths of the Baguala bay waters, Ambon island has been done at approximately monthly intervals during January to March and May to September 1994. Sampling was carried out during the day time by using a 200 µm meshed WP2 zooplankton net at 7 fixed stations. Eleven species of chaetognaths belonging to the genus Sagitta and 2 other species (Pterosagitta draco and Krohnitta pacifica) were recorded. A total of 23,960 individuals of chaetognaths were examined and of these 4,546 individuals contained prey in their guts. The copepods were the dominant prey of Sagitta enflata, accounting for 73.80% of the diet. It was found that the food containing ratio (FCR) of stage 2 of S. enflata was higher than the other stages, while the number prey per chaetognath (NPC) of stage 3 of S. enflata was higher than other stages, and the daily feeding rate (DFR) of S. enflata (all stages) recorded at stations in the mouth of the bay was slightly higher than at stations inside of the bay. The FCRs, NPCs, and DFRs of P. draco were lower than S. enflata, therefore the impact on the copepods community structure would be greatest in this season and the stations in the mouth of the bay.